The Relationship Between Learning Concentration and Understanding Level Through the Online Learning Process - Shao Xiaolin; Suwarsi Suwarsi; Pornman Inta; Asmarani Lathu Fajarina; Muflih Muflih; Listyana Natalia Retnaningsih; Santi Damayanti (Universitas Respati Yogyakarta, 2023)
Learning using online methods is indeed beneficial in several ways, but in nursing study programs, online learning faces several problems. Problems such as lack of focus and concentration become obstacles in how students understand course material, especially for topics related to skills. This study contributes to knowing the relationship between learning concentration and understanding level through an online learning process. This research is a type of quantitative research with a cross-sectional research design consisting of 130 respondents and using a total sampling technique, the instrument used is a questionnaire. The analysis used was the chi-square test. Data is collected online using the Google form. Univariate analysis shows that in the majority of students, when participating in online learning, the level of concentration of their learning is in the middle category (70%). For most students, when participating in online learning, their understanding level is in the low category (60.8%). The results of the bivariate analysis with the chi-square test showed that there was a relationship between learning concentration and the level of understanding through the online learning process with a p-value = 0.000. There is a relationship between learning concentration and the level of understanding when participating in online learning.